Thermal Variability in the Lublin Region During the Frost Wave in January 2017 - Krzyżewska, Agnieszka; Wereski, Sylwester; Nowosad, Marek (Annales Universitatis Mariae Curie-Sklodowska, sectio B – Geographia, Geologia, Mineralogia et Petrographia, 2019)
Frost waves are included to extreme weather phenomena – similarly as other phenomena of the type – constituting a threat for human health and life, as well as negatively affecting the natural environment. Frost wave is defined as a sequence of at least three consecutive days with minimum daily air temperature equal or lower than –15°C (Wibig et al. 2009). The aim of this paper is to examine the thermal conditions in the Lublin Region during particularly cold January of 2017. The adopted source materials were results of measurements of minimum and maximum daily air temperature and term values of air temperatures with a 1-hour time step from field meteorological stations of the Department of Hydrology and Climatology of the University of Maria Curie-Skłodowska (UMCS) located in the Lublin Region (Celejów, Leśniowice, Rybczewice, Wola Wereszczyńska, Guciów), as well as meteorological stations of the Institute of Meteorology and Water Management – National Research Institute IMGW-PIB (Siedlce, Terespol, Lublin-Radawiec, Włodawa, Sandomierz, Zamość, Kozienice). Frost wave in the Lublin Region was from 5 to 11 January. However, at the majority of stations (excluding the station in Terespol) on 9 January, the minimum daily air temperature was higher than –15°C. During this phenomenon, the lowest air temperature was recorded on 7 January in Guciów, and its value reached –25.3°C. The cause of this frost wave was the inflow of Arctic air from the north. Fale mrozów należą do ekstremalnych zjawisk pogodowych stanowiących – podobnie jak inne tego typu zjawiska – zagrożenie dla zdrowia i życia człowieka oraz wpływających niekorzystnie na środowisko przyrodnicze. Za falę mrozów przyjmuje się ciąg przynajmniej trzech kolejnych dni, podczas których minimalna dobowa temperatura powietrza była równa lub niższa od –15°C (Wibig i in. 2009). Celem niniejszej pracy jest zbadanie warunków termicznych na Lubelszczyźnie podczas szczególnie mroźnego stycznia 2017 r. Jako materiał źródłowy wykorzystano wyniki pomiarów minimalnych i ...